2023
DOI: 10.3390/molecules28041845
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Phenolic Compounds in Medicinal Plants—Natural Health Products for Human Health

Abstract: Phenolic compounds and flavonoids are potential substitutes for bioactive agents in pharmaceutical and medicinal sections to promote human health and prevent and cure different diseases. The most common flavonoids found in nature are anthocyanins, flavones, flavanones, flavonols, flavanonols, isoflavones, and other sub-classes. The impacts of plant flavonoids and other phenolics on human health promoting and diseases curing and preventing are antioxidant effects, antibacterial impacts, cardioprotective effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
89
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(89 citation statements)
references
References 515 publications
0
89
0
Order By: Relevance
“…Phenolic compounds are a large group of antioxidant compounds in SMs. They are widely distributed in the roots, leaves, stems, fruits, and other tissues of medicinal plants at different concentrations [40] . They can protect plant cells against oxidative stress by acting as ROS scavengers [41] and function efficiently in improving stress tolerance in plants [41,42] …”
Section: Resultsmentioning
confidence: 99%
“…Phenolic compounds are a large group of antioxidant compounds in SMs. They are widely distributed in the roots, leaves, stems, fruits, and other tissues of medicinal plants at different concentrations [40] . They can protect plant cells against oxidative stress by acting as ROS scavengers [41] and function efficiently in improving stress tolerance in plants [41,42] …”
Section: Resultsmentioning
confidence: 99%
“…OOC models can be utilized to investigate the interactions between nutraceuticals and relevant cellular targets to study the target engagement, modulation of signaling pathways, and downstream cellular responses. After target identification, nutraceutical compounds undergo efficacy screening and optimization. OOC-based safety assessment provides insights into the potential adverse effects and helps guide the selection of safe nutraceutical candidates for further development. OOC models can be utilized to study the absorption, distribution, metabolism, and excretion (ADME) properties of nutraceuticals.…”
Section: Types Of Ooc Models For Nutraceutical Testingmentioning
confidence: 99%
“…This involves identifying suitable materials, establishing quality control measures, and optimizing the fabrication processes to ensure consistent and reliable production of OOC devices. Regulatory compliance is crucial to ensure the safe and effective use of OOC technology for nutraceutical testing regulations, i.e., the Food and Drug Administration (FDA) in the United States or the European Medicines Agency (EMA) in Europe may classify OOC platforms as medical devices or in vitro diagnostics. …”
Section: Types Of Ooc Models For Nutraceutical Testingmentioning
confidence: 99%
“…Likewise, Abu Bakar et al (2009) studied the phytochemical and antioxidant activity of the seed and flesh of the fruit. Phenolic and flavonoid compounds possess antioxidant, anticancer, cardioprotective, and antibacterial properties, making them promising candidates for applications in the pharmaceutical and medical industries (Sun & Shahrajabian, 2023; Tungmunnithum et al, 2018). The experiment showed that the peel of Marang had a higher amount of total phenolic content (14.67 mg GAE/g) compared to the flesh (4.39 mg GAE/g).…”
Section: Current Utilization Of Marang Fruit Wastesmentioning
confidence: 99%